Partial melting of multiple mantle domains underneath the Paleo-Tethyan cold subduction zone triggered by slab rollback - Huang, Xiguang; He, Jun; Zhao, Jingxin; Dou, Jingzhao; Liu, Weiyong; Hu, Aimin; Liu, Ge; Ji, Yiru; Chen, Fukun; Li, Shuang-Qing (Lithos, 2024)
It is widely believed that the melting of mantle wedge in a subduction zone is triggered by the influx of fluids. However, experimental petrology studies have yielded conflicting results regarding temperatures for the wet solidus of mantle metasomatite, either below or above that of mantle wedge. In the latter case, the influx of fluids cannot trigger mantle melting, particularly in a cold subduction zone. Late Paleozoic magmatic rocks in the Western Yunnan Tethyan belt have been interpreted as being products of the first-stage subduction-related magmatism in the cold subduction zone and are thought to carry crucial information about mantle-wedge melting. Here, we report zircon ages and whole-rock geochemical data for these magmatic rocks to identify both the origin of the magmatism and the mechanism of mantle melting. Rock samples collected from the Nanlianshan complex and the Daxinshan Formation yielded zircon ages ranging from 303 Ma to 297 Ma. The samples can be classified into two groups based on geochemical features. Group I magmatic rocks have higher Ba/Th and lower Th/Nb ratios and depletion in NdHf isotopes [εNd(t) 2.9-5.0; εHf(t) 5.7-14.6], whereas Group II rocks show relatively lower Ba/Th and higher Th/Nb ratios and relative enrichment in NdHf isotopes [εNd(t) 0.7-4.0; εHf(t) 4.1-10.7]. The two groups of rocks may have originated from different mantle domains that were metasomatized by slab-derived aqueous fluids and by sediment-derived melts, respectively. We hypothesize that slab rollback during closure of the Paleo-Tethyan Ocean prompted mixing of different mantle domains; subsequently, the multiple mantle was heated by the laterally flowing asthenosphere, and partial melting occurred.
Online verfügbar: 14. November 2023, Artikelversion: 17. November 2023
Gesehen am 25.01.2024